1988
DOI: 10.1007/bf00273659
|View full text |Cite
|
Sign up to set email alerts
|

Pelizaeus-Merzbacher disease: identification of heterozygotes with magnetic resonance imaging?

Abstract: We report magnetic resonance imaging (MRI) findings in two obligate and four facultative carriers for the "classical" X-linked form of Pelizaeus-Merzbacher disease (PMD). In T2-weighted images MR revealed bilateral multiple areas with signal hyperintensity in the periventricular and subcortical white matter in five women. Until suitable and closely linked DNA probes are found for heterozygote determination, MRI may represent a suitable means for carrier detection in individuals at risk in PMD families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Likewise, a tentative diagnosis of PMD was made in our patient given the signs of hypomyelination detected on brain MRI and the altered pattern of the auditory brain evoked potentials. Although minor neurological and imaging signs are reported in obligate carriers for PMD [Boltshauser et al, 1988;Huygen et al, 1992], the disease is known to affect exclusively males. About 25% of patients show point mutations in the PLP protein, mapped to Xq22.…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, a tentative diagnosis of PMD was made in our patient given the signs of hypomyelination detected on brain MRI and the altered pattern of the auditory brain evoked potentials. Although minor neurological and imaging signs are reported in obligate carriers for PMD [Boltshauser et al, 1988;Huygen et al, 1992], the disease is known to affect exclusively males. About 25% of patients show point mutations in the PLP protein, mapped to Xq22.…”
Section: Discussionmentioning
confidence: 98%
“…MR findings in PMD and other leukodystrophies have recently been reported [8][9][10][11][12]. Four patients with PMD, ages 7 to 18, demonstrated increased peripheral white matter signal compared with gray matter on T2-weighted images, which is the reverse of the normal relationship at these ages, as well as decreased signal intensity in the basal ganglia.…”
Section: Discussionmentioning
confidence: 93%
“…The former made increasingly probable the antemortem detection of leukodystrophy in general, while our study [Trofatter et al, 19891 showed that at least one mutation in PLP was tightly linked to, if not causative of, PMD. MRI was also suggested as a method for carrier detection by Boltshauser et al [1988], but disclosure of the mutation in that family by ourselves [Pratt et al, 19911 and Weimbs et al [1990] showed that a genetically normal female had been misidentified as a carrier by MRI. Even the detection of mutation(s) in the exons ofPLP is useful only in those families, perhaps one third of those diagnosed clinically, in which such a mutation is found in PLP.…”
Section: Discussionmentioning
confidence: 98%